The Cassava Biotechnology Network (CBN) and cassava biotechnology research - Thro, Ann Marie; Roca, W.; Henry, Guy (International Center for Tropical Agriculture, 1995)
The Cassava Biotechnology Network (CBN) was formed in response to the need for a forum to discuss cassava biotechnology issues and to foster cassava biotechnology research on priority subjects. In CBN, the experience and efforts of many different organizations and countries are pulled together to collaborate in research and to share techniques, results, genetic materials, and training opportunities. Through broad-ranging dialogue across disciplines, CBN has defined a set of cassava biotechnology research priorities. The objectives of the Cassava Biotechnology Network are to promote integration of end-user priorities in cassava biotechnology research planning, to stimulate cassava biotechnology research on topics of established priorities, and to foster free exchange of information on cassava biotechnology research, including techniques, results, and materials. CBN organizes biennial scientific meetings and publishes scientific proceedings, a semiannual newsletter, and other material. Within CBN, informal working groups have formed around several of the priority cassava biotechnology research themes or areas, according to the technical demands of each theme and the comparative advantages of various laboratories. CBN supports these working groups through facilitating contact and encouraging meetings as necessary to clarify progress and coordinate planning